Interplay of miRNAs and Canonical Wnt Signaling Pathway in Hepatocellular Carcinoma - Nie, Xiaobo; Liu, Yiran; Chen, Wei-Dong; Wang, Yan-Dong (Frontiers in Pharmacology, 2018)
Hepatocellular carcinoma is one of the leading causes of cancer death worldwide and the activation of canonical Wnt signaling pathway is universal in hepatocellular carcinoma patients. MicroRNAs are found to participate in the pathogenesis of hepatocellular carcinoma by activating or inhibiting components in the canonical Wnt signaling pathway. Meanwhile, transcriptional activation of microRNAs by canonical Wnt signaling pathway also contributes to the occurrence and progression of hepatocellular carcinoma. Pharmacological inhibition of hepatocellular carcinoma pathogenesis and other cancers by microRNAs are now in clinical trials despite the challenges of identifying efficient microRNAs candidates and safe delivery vehicles. The focus of this review is on the interplay mechanisms between microRNAs and canonical Wnt signaling pathway in hepatocellular carcinoma, and a deep understanding of the crosstalk will promote to develop a better management of this disease.